Aspects of the Chi-square and Kolmogorov-Smirnov goodness-of-fit tests with special reference to the continuous case - Cilliers, Hendrika Margaretha (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Comm.) -- University of Stellenbosch, 1996.